Advanced Engineering Mathematics - Kreyszig, Erwin; Herbert Kreyszig; Edward J. Norminton (India : John Wiley, 2011)
Mathematics and Statistics
Keywords: Engineering mathematics; Differential equations; Vector calculus; Graphs; Statistics